FAKTOR YANG BERPENGARUH TERHADAP MATERNAL - FETAL ATTACHMENT - Evi Wahyuntari; Tri Hapsari Listyaningrum; Siti Istiyati (MEDIA ILMU KESEHATAN, 2019)
Background: Pregnancy, childbirth and postpartum is a transition period for a woman and is a complex life event that affects the biological, psychological, and social life experienced by the mother. Therefore the need to cultivate an inner bond between mother and baby or known as maternal fetal attachment (MFA). Objective: Aim of this study was to find factors that influence MFA in pregnant women. Methods: cross sectional study. The study was conducted at PKU Muhammadiyah Yogyakarta. Population is pregnant women routine ANC visits at the obstetric clinic. 100 respondents determined by the method of consecutive sampling. Inclusion criteria of pregnant women with a gestational age of 20-38 weeks, do not have high risk of pregnancy, no complications in pregnancy, and willing to become respondents. Exclusion criteria mothers who were not willing to become respondents. Data collection used a questionnaire consisting of basic data questionnaires for pregnant women, Socio demographic data, reproductive history, Pregnancy, PAI questionnaire , SSQ questionnaire. Results: The planned pregnancy had an effect on the MFA with indigo p <0.05 OR 6, 44 which means that the planned pregnancy had an effect of 6.44 times on the MFA score. while age, education, parity, occupation has no effect on the MFA score Conclusion: Planed pregnacy had an effect on MFA score in PKU Muhammadiyah Yogyakarta